2016
DOI: 10.1074/jbc.m116.750034
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Peroxidase Catalyzed Protein Carbamylation Participates in Asthma

Abstract: The biochemical mechanisms through which eosinophils contribute to asthma pathogenesis are unclear. Here we show eosinophil peroxidase (EPO), an abundant granule protein released by activated eosinophils, contributes to characteristic asthma-related phenotypes through oxidative posttranslational modification (PTM) of proteins in asthmatic airways through a process called carbamylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 94 publications
1
23
0
1
Order By: Relevance
“…EPX itself can generate antibacterial reactive oxygen metabolites 21,67 and has been implicated directly in specific nitrosylation and carbamoylation reactions in vivo. 68,69 Furthermore, as shown here, EPX −/− mice display diminished recruitment of eosinophils to the lungs, and, of the eosinophils that are recruited, a smaller proportion are TLR4 + . Given these findings, we asked whether eosinophils, as a component of A. alternatamediated inflammation, might be effective in clearing gram-negative nontypeable Haemophilus influenzae (NTHi) from the airways, and whether EPX deficiency might have an impact on this activity; this was addressed via the protocol shown in Fig.…”
Section: A Alternata-challenged Epx −/− Mice Were No Less Effective supporting
confidence: 55%
See 1 more Smart Citation
“…EPX itself can generate antibacterial reactive oxygen metabolites 21,67 and has been implicated directly in specific nitrosylation and carbamoylation reactions in vivo. 68,69 Furthermore, as shown here, EPX −/− mice display diminished recruitment of eosinophils to the lungs, and, of the eosinophils that are recruited, a smaller proportion are TLR4 + . Given these findings, we asked whether eosinophils, as a component of A. alternatamediated inflammation, might be effective in clearing gram-negative nontypeable Haemophilus influenzae (NTHi) from the airways, and whether EPX deficiency might have an impact on this activity; this was addressed via the protocol shown in Fig.…”
Section: A Alternata-challenged Epx −/− Mice Were No Less Effective supporting
confidence: 55%
“…EPX itself can generate anti-bacterial reactive oxygen metabolites [21, 67] and has been implicated directly in specific nitrosylation and carbamoylation reactions in vivo [68, 69]. Furthermore, as shown here, EPX -/- mice display diminished recruitment of eosinophils to the lungs, and, of the eosinophils that are recruited, a smaller proportion are TLR4 + .…”
Section: Resultsmentioning
confidence: 63%
“…However, the extensive degranulation in I5/hE2 mice leading to the release of EPX overcomes this limitation and in doing so demonstrated that the release of EPX is actually a modifier of IL-13-mediated events that enhances GM/MA. Our recent mechanistic studies demonstrating that the peroxidase activities of EPX mediate carbamylation of lung proteins provide a mechanistic explanation of this effect (62). Specifically, these carbamylated proteins were shown to have direct agonist activities on airway epithelia leading to goblet cell metaplasia and increased mucin gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that IL-13 levels in OVA-treated WT and I5/hE2 mice were virtually identical, this suggests that the release of granule proteins in the lungs of I5/hE2 mice enhances the GM/MA linked with IL-13 expression. Indeed, our recent studies demonstrating that the peroxidase activities of EPX in the lung elicit a posttranslational protein modification, known as carbamylation, provides a mechanism of the enhanced GM/M observed in I5/hE2 relative to I5/hE2/MBP-1 2/2 /EPX 2/2 mice [40]. Specifically, these new studies have shown that carbamylated proteins have direct agonist activities on airway epithelial cells, leading to goblet cell metaplasia and increased mucin gene expression.…”
Section: Discussionmentioning
confidence: 94%